Optimization Of Zakat Mal In Poverty Reduction Efforts - Organdy , Organdy; Iwan Setiadi (Cita konsultindo, 2024)
This article aims to evaluate the realization of zakat mal in poverty alleviation efforts in Indonesia, especially in Sibak Village, Ipuh District, Mukomuko Regency, Bengkulu Province. This article investigates the factors that influence the suboptimal zakat mal, namely the availability and accessibility of human resources, community participation, and services provided by zakat institutions. This article also examines the impact of zakat mal realization on poverty alleviation in Sibak Village, Ipuh District. The method used in this research is the SWOT analysis method, which uses internal environmental factors (strengths and weaknesses) and external environmental factors (opportunities and threats). The results of this study are expected to provide a better picture of the realization of zakat mal in poverty alleviation efforts in Sibak Village, Ipuh District. In addition, the research results can also help policy makers to increase the realization of zakat mal in Sibak Village, Ipuh District.